«Weder Empirist noch Dogmatiker». Lukács interprete di Lenin - Gargani, Matteo (——— Materialismo Storico ——— Rivista di filosofia, storia e scienze umane, 2018)
This paper examines Lukács’ interpretation of Lenin, with particular focus on his Lenin: A Study on the Unity of his Thought (1924), and the Postscript which was added to the book in January 1967. From 1924 onward, Lukács mainly focuses on the methodological basis of Lenin’s political thought, which vital point lays in applying the category of totality in order to grasp the complexity of the socio-historical conjuncture. In addition, Lukács deals with some ethical aspects of Lenin’s personality, i.e. his human attitude. The ethical aspects are but the weakest point in Lukács’ interpretation. Diametrically opposed to any form of decisionism, Lenin embodies for Lukács both a politician and a political scientist. Keywords: Lukács; Lenin; Totality; Method; Attitude; Socialism.